Determinasi financial distress: Peran profitabilitas, likuiditas, dan leverage pada industri bahan konstruksi - Mustamin, Riandi; Ida, Ida (Universitas Tarumanagara, 2025)
This study aims to investigate the impact of profitability, liquidity, and leverage on financial distress in construction materials companies. The construction industry plays a vital role in national development. Yet, it remains vulnerable to financial pressure due to factors like rising raw material costs and high dependency on imported inputs. This research employs a quantitative approach, utilizing binary logistic regression, based on financial data from 11 companies listed on the Indonesia Stock Exchange during the 2021–2024 period, resulting in 44 observations. Financial distress is defined by operating losses sustained for two consecutive years. The results show that leverage (measured by Debt to Asset Ratio) has a positive and significant effect on financial distress, meaning that a higher proportion of debt in the capital structure increases the likelihood of financial distress. On the other hand, profitability (measured by Return on Assets) and liquidity (measured by Current Ratio) show no significant relationship with financial distress. These findings suggest that poorly managed debt is the primary driver of financial difficulties, while profit and liquid assets alone are insufficient to prevent financial distress. This study highlights the importance of managing capital structure wisely and avoiding excessive reliance on debt, especially in an industry exposed to operational and economic uncertainty. The results are expected to serve as useful input for financial management strategies and contribute to academic literature in corporate finance. Penelitian ini dilakukan untuk melihat bagaimana kondisi keuangan perusahaan bahan konstruksi bisa dipengaruhi oleh profitabilitas, likuiditas, dan leverage. Industri ini dianggap penting karena mendukung pembangunan nasional, tetapi juga rentan mengalami tekanan keuangan, terutama akibat kenaikan harga bahan baku dan ketergantungan pada impor. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis regresi logistik terhadap 11 perusahaan yang terdaftar di BEI selama periode 2021–2024, dengan total 44 observasi. Financial distress diklasifikasikan berdasarkan kondisi rugi operasional selama dua tahun berturut-turut. Hasil analisis menunjukkan bahwa leverage (DAR) berpengaruh positif dan signifikan terhadap financial distress, yang berarti semakin besar proporsi utang dalam struktur pembiayaan perusahaan, maka semakin tinggi pula kemungkinan perusahaan mengalami tekanan keuangan. Sebaliknya, profitabilitas (ROA) dan likuiditas (CR) tidak berpengaruh signifikan terhadap financial distress. Dari sini bisa disimpulkan bahwa utang yang tidak terkelola dengan baik menjadi faktor utama penyebab risiko keuangan, sementara laba dan aset lancar tidak cukup kuat sebagai penyangga terhadap tekanan finansial. Hasil ini memberikan gambaran bahwa perusahaan di sektor konstruksi perlu lebih berhati-hati dalam mengatur struktur modal dan tidak semata-mata bergantung pada utang untuk menjaga keberlangsungan usahanya. Penelitian ini diharapkan dapat menjadi bahan pertimbangan manajerial dan literatur tambahan di bidang keuangan.